Innovative Learning of Fiction Writing through an E-Module Integrating Local Wisdom “Andum Alpukat” - Sumiyarsih, Ninuk; Subrata, Heru; Hendratno, Hendratno; Mariana, Neni; Rachmadyanti, Putri (Journal of Language and Literature Studies, 2025)
The use of E-Modules is not new for educators; however, there remains a limited number of studies that specifically develop Flipbook-based interactive modules integrating local cultural values to enhance elementary students’ fiction writing skills. This study aims to evaluate the feasibility of the interactive E-Module “Andum Alpukat” as a learning medium, employing a research and development (R&D) design that combines qualitative and quantitative approaches. The development process involved validation by material experts, module design experts, peer reviewers, and trials conducted individually, in small groups, and in large groups with fifth-grade students at SD Negeri Pulosari 1 Bareng Jombang. The findings reveal that the module received a feasibility score of 75% from material experts, 93.75% from design experts, 97.5% from peer reviewers, and 89.99% based on student responses. These results indicate that the “Andum Alpukat” interactive E-Module is both feasible and effective in improving students’ fiction writing skills. The study concludes that a modified Flipbook aligned with students’ learning needs can produce a high-quality and engaging instructional medium. The implications of this study suggest that similar modules have strong potential for broader implementation within Merdeka Curriculum–oriented classrooms and for fostering culturally grounded creativity in fiction writing to strengthen meaningful learning experiences.